IMPLEMENTASI SISTEM PENGENALAN WISATA BAHARI BERBASIS WEBSITE KABUPATEN MAJENE - Dian Megah Sari; Asmawati S (JURNAL TEKNIK INFORMATIKA, 2020)
The area of Majene Regency is dominated by waters and marine areas with many marine tourism destinations so that it is well known in several Majene regency areas but is less explored so that it is not known by some people due to the lack of information facilities, for this reason the implementation of a website in the introduction of marine tourism in Majene Regency is needed. This website application development aims to facilitate users in accessing marine tourism information in Majene Regency. An application designed and invincible with the needs of tourists in order to get information on the tourist destinations you want to visit. The design of this website is carried out using the Waterfall method, built with the Sublime Text 3 script language, PHP and Xampp 7.1 as the database, and the testing system uses a blackbox testing so as to produce a special marine tourism application that is feasible and can be accessed online.